1987
DOI: 10.1002/jhet.5570240635
|View full text |Cite
|
Sign up to set email alerts
|

Studies on heterocyclic enamines: New syntheses of 4H‐pyranes, pyranopyrazoles and pyranopyrimidines

Abstract: The behaviour of several 2‐amino‐3‐cyano‐4H‐pyran derivatives toward a variety of nucleophilic reagents is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…For example, 1a was obtained in 86 % yield after 10 min of ultrasound irradiation, whereas 1a was isolated in 80 % yield after 3 h with a traditional heating method. [6] Photochemical Properties of the 2-Amino-3-cyano-4-aryl-4H-pyrans Photostability of 2-Amino-3-cyano-4-aryl-4H-pyrans The UV-vis absorption spectra of 1a, 1b, 1c, 1d, and 1e in THF at a concentration of 5 Â 10 À5 M are shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 1a was obtained in 86 % yield after 10 min of ultrasound irradiation, whereas 1a was isolated in 80 % yield after 3 h with a traditional heating method. [6] Photochemical Properties of the 2-Amino-3-cyano-4-aryl-4H-pyrans Photostability of 2-Amino-3-cyano-4-aryl-4H-pyrans The UV-vis absorption spectra of 1a, 1b, 1c, 1d, and 1e in THF at a concentration of 5 Â 10 À5 M are shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…Thin-layer chromatography (TLC) was conducted on silica gel 60 F254 plates (Merck KGaA). 1 H and 13 C NMR spectra were recorded on a Bruker Avance 400 spectrometer at 400 and 100 MHz, respectively, using CDCl 3 or DMSO-d 6 as the solvent and tetramethylsilane (TMS) as the internal standard. The melting points were determined on a XT-5A digital melting point apparatus and are uncorrected.…”
Section: Methodsmentioning
confidence: 99%
“…We suggest for the synthesis of 6 , 7 , 15 , 17 , 19 , and 21 a new direction by the alkylation of 5‐acetyl‐2‐amino‐6‐methyl‐4‐phenyl‐4 H ‐pyran‐3‐carbonitrile ( 10 ). According to the literature, by the interaction of different active methylene compounds with the 10 , Elnagdi et al observed the recyclization of the pyran cycle, yielding of corresponding products. However, during the reaction of 10 with acetoacetate in ethanol in the presence of a base, such as triethylamine or piperidine, the replacement of methyl by the ethoxy fragment was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, 2-amino-4-aryl-3-cyano-4H-pyrans were synthesized by the cyclization of arylidenemalononitriles and active methylene compounds in the presence of organic bases such as piperidine, 14 pyridine, 15 triethylamine 16,17 . Most of these methods involve use of volatile solvents and require longer reaction time (~ 12 h) and difficult to recover catalyst.…”
Section: Introductionmentioning
confidence: 99%